Viewpoint: water, agriculture and poverty in an era of climate change: why do we know so little? - Balasubramanya, Soumya; Stifel, David (Elsevier, 2020)
Understanding the complex relationship between water, agriculture and poverty (WAP) is essential for informed policy-making in light of increasing demand for scarce water resources and greater climatic variability. Yet, our understanding of the WAP nexus remains surprisingly undeveloped and dispersed across multiple disciplines due to conceptual (biophysical and economic) and measurement issues. We argue that water for agriculture will need to be better managed for it to contribute to reductions in poverty and vulnerabilities. Moreover, this management will need to consider not just quantities of water, but the quality of the water and the multiple agricultural and non-agricultural uses. For this reason, expanding research in WAP needs to involve interdisciplinary efforts. We identify three key knowledge gaps in WAP that are particularly pressing in light of greater climatic variability. These are climate change adaptation, over-abstraction of groundwater, and water quality.